Epistemological references of Islamic intellectual projects Nasr Hamed Abu Zeid read by Michel Foucault - Abdelkader, Hamida (Journal of Human Sciences, 2020)
This article aims to deconstruct the references that fueled Islamic intellectual projects according to an epistemological vision, including several projects such as the project of Hussein Marwa, Mohammed Abed Al Jabri, Tayeb Tizini, and Mohammed Arkoun, etc. That of Nasr Hamed Abu Zeid (1943-2010): is one of these projects, which will be our model in this article, according to the archaeological approach of the French philosopher and thinker Michel Foucault (1926-1984), who tries to use the fossil methodology to find the most important references. Thus, this article is an attempt to understand the fundamentals of one of these projects which, without understanding them, can not be evaluated or judged, and can not measure their extent, and their contribution to Arab thought. Islamic and, subsequently, to human thought.